Accountability as a function of power relationships in public governance networks - Peter Eckersley; Katarzyna Lakoma; Pete Murphy; Tom Caygill; Charlotte Pell (Public Administration, 2024)
In public governance, power and accountability are inextricably linked. However, although an integrated exploration of these concepts could enhance our understanding of how governance operates, few studies have examined them together. Drawing on resource dependency theory, we suggest that power relationships within networks shape accountability and have a concomitant impact on the prevailing governance paradigm. Specifically, where principals possess important resources that enable them to exercise power over agents and hold them to account through hierarchical mechanisms, Traditional Public Administration approaches predominate. Where resources are diffused within elite networks in New Public Management contexts, individual actors can exercise greater power to achieve their objectives, and accountability arrangements become increasingly multidirectional and complex. Finally, if resources are shared across society as in the New Public Governance paradigm, actors generate power with each other to achieve shared goals, and accountability relationships are more horizontal with a focus on learning.
Keywords: 300